Real-time visualization of autophagy by monitoring the fluctuation of lysosomal pH with a ratiometric two-photon fluorescent probe. Issue 12 (22nd January 2019) - Ning, Peng; Hou, Liling; Feng, Yan; Xu, Guoyong; Bai, Yuyuan; Yu, Haizhu; Meng, Xiangming
Abstract : A ratiometric two-photon fluorescent probe (Lyso-MPCB ) was developed for visualizing autophagy by real-time imaging the fluctuation of lysosomal pH. Abstract : A benzimidazole-decorated two-photon fluorescent probe (Lyso-MPCB ) based on the p -methoxyphenylacetylene-substituted carbazole was developed for detecting lysosomal pH with a double-channel signal, which can be used to visualize autophagy by real-time imaging the fluctuation of the pH in the lysosomes.